2019
DOI: 10.1021/acsnano.9b03792
|View full text |Cite
|
Sign up to set email alerts
|

Brightening of Long, Polymer-Wrapped Carbon Nanotubes by sp3 Functionalization in Organic Solvents

Abstract: The functionalization of semiconducting single-walled carbon nanotubes (SWNTs) with sp 3 defects that act as luminescent exciton traps is a powerful means to enhance their photoluminescence quantum yield (PLQY) and to add optical properties. However, the synthetic methods employed to introduce these defects are currently limited to aqueous dispersions of surfactant-coated SWNTs, often with short tube lengths, residual metallic nanotubes, and poor film-formation properties. In contrast to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
129
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(142 citation statements)
references
References 66 publications
7
129
0
6
Order By: Relevance
“…Adding pyridine groups to the backbone seems to be able to disperse larger diameter SWNTs, such as those produced by laser vaporization or arc discharge [ 36 , 51 ]. The extracted s-SWNTs have both high purity and high yield, with a reduced diameter abundance, which is more desired for electrical and optical uses [ 52 , 53 , 54 , 55 , 56 ]. Tange et al found that PFO-Py (P4) could selectively extract (13, 5) SWNT [ 52 ].…”
Section: Conjugated Polymers Used For Separationmentioning
confidence: 99%
“…Adding pyridine groups to the backbone seems to be able to disperse larger diameter SWNTs, such as those produced by laser vaporization or arc discharge [ 36 , 51 ]. The extracted s-SWNTs have both high purity and high yield, with a reduced diameter abundance, which is more desired for electrical and optical uses [ 52 , 53 , 54 , 55 , 56 ]. Tange et al found that PFO-Py (P4) could selectively extract (13, 5) SWNT [ 52 ].…”
Section: Conjugated Polymers Used For Separationmentioning
confidence: 99%
“…The deep optical traps (100–200 meV) lead to a strong red shift of the emission and facilitate high-purity single-photon emission at room temperature. 47 , 48 These defects can be created synthetically by arylation, 43 , 44 alkylation, 49 or covalent oxygen doping. 47 Depending on the binding configuration, two main types of defects have been identified, commonly named E 11 * (1.05 eV or 1180 nm) and E 11 * – (0.95 eV or 1300 nm) for (6,5) nanotubes (see Figure 1 , right).…”
mentioning
confidence: 99%
“…[30] Diese Technik ermçglichte auch die Abstimmung der Defektfluoreszenz sowohl in Bezug auf die Intensitäta ls auch auf die Emissionswellenlänge über verschiedene Substituenten am Aryl/Alkyl-Defekt. [31][32][33][34] In den letzten Jahren wurde über eine Reihe verschiedener Sauerstoff-und Aryl-Defekte berichtet, die nun sehr vielversprechende Werkzeuge fürd ie Erzeugung von helleren/modifizierten SWCNTs, [31,35,36] pH- [37] or Saccharid [38] -Sensoren, kurzen fluoreszierenden SWCNTs fürd ie hochauflçsende Mikroskopie [39] oder Einzelphotonenquellen für das Quanten-Computing sind. [40,41] Darüber hinaus verschiebt dieses neue Defekt-induzierte Fluoreszenzsignal die Emission noch weiter in das Biotransparenzfenster,w as zu noch besseren Gewebepenetrationseigenschaften führt.…”
Section: Einführungunclassified